2014
DOI: 10.1371/journal.pone.0089088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Switching from Stavudine to Raltegravir on Subcutaneous Adipose Tissue in HIV-Infected Patients with HIV/HAART-Associated Lipodystrophy Syndrome (HALS). A Clinical and Molecular Study

Abstract: HIV-1/HAART-associated lipodystrophy syndrome (HALS) has been associated with exposure to stavudine (d4T) through mitochondrial dysfunction. We performed a 48-week study to assess the effects of switching from d4T to raltegravir (RAL) on metabolic and fat molecular parameters of patients with HALS. Forty-two patients with HALS and a median exposure to d4T > 7 years were switched to RAL and followed for 48 weeks. Fasting metabolic tests, HIV RNA, CD4 cell count, and fat measured by DEXA were obtained at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…A total of 21 articles were included in this study: 10 observational cohort studies , six clinical trials , two cross‐sectional studies , one experimental study , one observational prospective study and one case report .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 21 articles were included in this study: 10 observational cohort studies , six clinical trials , two cross‐sectional studies , one experimental study , one observational prospective study and one case report .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding drug combinations, the participants were initiating or switching to treatment with fusion inhibitors , C‐C chemokine receptor type 5 (CCR5) inhibitors or integrase inhibitors . The three studies showed the emergence of major adverse effects (Table ), with the highest incidence of major adverse effects found for exposure to CCR5 binding inhibitors and the lowest incidence of lipodystrophy found for integrase inhibitors . Circulating markers of liver damage were also observed .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New antiretroviral agents with milder AT toxicity have promising effects in lipodystrophy. In fact, switching from nucleoside reverse transcriptase inhibitors to Raltegravir, the first integrase inhibitor, was associated with recovery of subcutaneous AT mass [12]. Notoriously, beneficial effects on adipose mass do not necessarily correlate with improved insulin resistance [12].…”
Section: Haart-associated Lipodystrophymentioning
confidence: 99%
“…In the SPIRAL parent study, switch to raltegravir was associated with significant reductions in hs-CRP, monocyte chemotactic protein (MCP)-1, IL-6, and TNF-α but not IL-10 or adiponectin, and it is not clear to what extent changes in adipose tissue explain the changes in inflammatory markers [128]. In contrast, a switch to raltegravir from stavudine therapy among lipodystrophic individuals resulted in improvements in whole body and limb fat quantity, trunk/limb fat ratio and fat mass index, with restoration of mtDNA and adiponectin levels [52]. …”
Section: Discussionmentioning
confidence: 99%